(untitled) (American Journal of Management, 2022)
“Command and Control,” or “C2,” is the theoretical part of a set of means and methods (C4ISR) for managing large human complex systems usually engaged in operations and whose lack of effective management can have highly undesirable or even disastrous consequences. It is mainly used in military context. This article investigates the theory that supports C2 principles and C4ISR practice as well as their role in the regulation of complexity of regulating movement while being itself a generator of its complexity. The present analysis belongs to cybernetics and explores military applications and the status of C2 as a system of systems to control complexity.